Cognitive Linguistics Critical Discourse Studies (CL-CDS) Puisi Awas Mudah Terbakar Karya Rachmat Hidayat Mustamin - Mazhud, Nurfathana (Fakultas Sastra Universitas Muslim Indonesia, 2023)
Cognitive Linguistics Critical Discourse Studies (CL-CDS) in Rachmat Hidayat Mustamin's poem Beware of Combustion is analyzed by interpreting conceptually cognitive psychological-oriented meanings. This study aims to analyze the text of poetry by describing the conceptual meaning of cognitive psychology. Furthermore, the structure of knowledge is described based on experience and environmental observations that are interpreted openly. In analyzing qualitative data, namely examining the text of poetry, conducting data reduction, compiling data coding, and concluding data. The results of the study show that in the text dimension the presentation of the poem Awas Mudah Terbakar discusses affirmations that give a warning of something that is quickly provoked. Satire conveyed as a form of social protest that questions a condition. Many people stay silent with everything that happens even though they are constrained by the interests of a particular group, making it difficult for them to develop further. The message of social cognition from the poem Awas Mudah Terbakar is conveyed using parables and motivating statements with implied word choices.